Removal of nitrobenzene from aqueous solution by adsorption onto carbonized sugarcane bagasse - Dunqiu Wang; Huijun Shan; Xiaojie Sun; Hongxia Zhang; Yanhua Wu (Adsorption Science & Technology)
A sorbent was prepared by charring sugarcane bagasse (SCB) and used to remove nitrobenzene from aqueous solution. The surface area, morphology, and functional groups of the adsorbent were characterized by Brunauer–Emmett–Teller method, scanning electron microscopy, and Fourier transforms infrared spectroscopy. Analysis indicated that oxygen-containing functional groups, such as C = O, –OH, –COOH, and C–O–C, may be involved in the adsorption process. The adsorption of nitrobenzene was investigated under different operating conditions, including adsorbent dosage, initial nitrobenzene concentration, pH, and contact duration. Four kinetic models were applied to describe the adsorption process. Results revealed that the optimal sorbent mass was 0.3 g/50 mL at pH 5.8 and 25°C. The kinetic data obeyed the pseudo-second-order kinetic model ( R 2  > 0.9965). In addition, Langmuir and Freundlich isotherm models were employed to describe the adsorption equilibrium. The Freundlich model presented better fitting for the adsorption equilibrium, suggesting that the carbonized SCB surface had a heterogeneous nature. The maximum adsorption capacities calculated by the Langmuir model were 38.27, 41.72, and 44.70 mg/g at 25°C, 35°C, and 45°C, respectively. The calculated values of ΔG 0 and ΔH 0 indicated the spontaneous and exothermic nature of the adsorption process at the considered temperature range. The adsorption mechanism of nitrobenzene onto carbonized SCB cannot be described either as physical adsorption or chemisorption. This study demonstrated that SCB biochar is a potential sorbent for removing nitrobenzene from aqueous solutions.